Comprehensive micropollutant screening using LC-HRMS/MS at three riverbank filtration sites to assess natural attenuation and potential implications for human health. (1st December 2018) - Hollender, Juliane; Rothardt, Judith; Radny, Dirk; Loos, Martin; Epting, Jannis; Huggenberger, Peter; Borer, Paul; Singer, Heinz
Abstract: Riverbank filtration (RBF) is used worldwide to produce high quality drinking water. With river water often contaminated by micropollutants (MPs) from various sources, this study addresses the occurrence and fate of such MPs at three different RBF sites with oxic alluvial sediments and short travel times to the drinking water well down to hours. A broad range of MPs with various physico-chemical properties were analysed with detection limits in the low ng L −1 range using solid phase extraction followed by liquid chromatography coupled to tandem high resolution mass spectrometry. Out of the 526 MPs targeted, a total of 123 different MPs were detected above the limit of quantification at the three different RBF sites. Of the 75–96 MPs detected in each river, 43–59% were attenuated during RBF. The remaining total concentrations of the MPs in the raw drinking water accounted to 0.6–1.6 μgL −1 with only a few compounds exceeding 0.1 μgL −1, an often used threshold value. The attenuation was most pronounced in the first meters of infiltration with a full elimination of 17 compounds at all three sites. However, a mixing with groundwater related to regional groundwater flow complicated the characterisation of natural attenuation potentials along the transects. Additional non-target screening at one site revealed similar trends for further non-target components. Overall, a risk assessment of the target and estimated non-target compound concentrations finally indicated during the sampling period no health risk of the drinking water according to current guidelines. Our results demonstrate that monitoring of contamination sources within a catchment and the affected water quality remains important in such vulnerable systems with partially short residence times. Graphical abstract: Image 1 Highlights: 123 of 500 micropollutants were detected with LC-ESI-HRMS/MS in surface and groundwater samples. About 50% of the micropollutants were attenuated during riverbank filtration with short residence times. 17 micropollutants were attenuated >50% at all 3 sites within <24 h and 13 persisted >50%. Target and non-target screening of raw water indicate no significant human health risk.